Acessos, reciprocidades e inclusões: estudo sobre as relações entre redes de assistência e famílias de grupos populares em Pelotas / RS - Pereira, Fabíola Mattos (2008)
This study is aimed to concerns related with the dynamics of life of the working class groups, from the relations of reciprocity established between the families and the social assistance networks organized in two suburbs of the city of Pelotas / RS. The concern which has motivated the execution of this study has contributed in the sense of relating the ethnocentric points of view, that in the past used to judge the working class groups as being alienated and without class awareness and nowadays continue to judge, although in other terms, a new outfit for an old degenerated vision when it comes to thinking in the inequalities in the Brazilian society. Having as a starting point the ethnocentric perspective, it will be presented the logic included in these relations of reciprocities where the triple obligation of giving, receiving and returning is presented as a strategy in order to analyze the inclusions in the social assistance programs. The ethnographic method was adopted with the objective of orienteering the interpretation of the field of study, and has contributed in the sense of mapping the assistance network actions organized in the scope investigated, and present the point of view of the families, professionals and volunteers. This study has used two sets of data: quantitative, obtained from domiciliary registers of all the beneficiaries of the Bolsa Familia program, and qualitative which was conducted in two suburbs of the city of Pelotas, Loteamento Dunas and Vila Pestano.